A Model for Igniter Mass Flow Rate History Evaluation for Solid Rocket Motors - Yanjie Ma; Futing Bao; Weihua Hui; Yang Liu; Yijie Gao (International Journal of Aerospace Engineering)
This paper describes a zero-dimensional model for evaluating the mass flow rate history of a solid rocket motor igniter. Based on the results of an igniter-firing experiment, in which the igniter is the only source of combustion gas and no propellant is ignited, the proposed model can be used to compute the mass flow rate of the igniter. Different species and temperature-dependent properties, such as the specific heat for each species, are considered. The coupling between the flow field variables in the combustion chamber and the heat transfer at the gas-solid interface is computed in a segment way. Calculations are performed for different species and properties, and the errors are discussed. Using the computed igniter mass flow rate as a boundary condition, a two-dimensional calculation is performed for validation purposes. The results are in good agreement with experimental data. The proposed model can be used to provide reasonable boundary conditions for solid rocket motor simulations and to evaluate the performance of igniters. Although derived on the basis of a small-scale solid rocket motor, the model has the potential to be used in large-scale systems.